Influence of root depth and the post type on Knoop hardness of a dualcured resin cement - Murilo de Sousa Menezes; Adeliana Garcia Veríssimo; Rodrigo Borges Fonseca; André Luís Faria Silva; Luís Roberto Marcondes Martins; Carlos José Soares (Universidade Estadual de Campinas, 2016)
Fiber posts are usually luted to the root canal with dual-cured resin cements. However, some of these cements require light-activation in order to reach optimal degree of cure. The aim of this study was to evaluate the effect of the fiber post type on microhardness of a dualcured resin cement used for luting these posts. After endodontic treatment, four fiber post types were luted to the root canal of bovine incisors with RelyX ARC. The samples were sectioned in order to obtain four slices, representing different depths (0.0; 2.5; 5.0; 7.5 and 10.0mm). Knoop microhardness testing was performed in each slice. The data were submitted to split-plot ANOVA and Tukey post-hoc tests. An additional sample per fiber post type was used to analyze bonding interface by SEM. At the depths of 0 and 2.5 mm, the resin cement presented the highest hardness values. The lowest values were observed at the 10 mm depth, and the resin cement presented intermediary hardness means at the depths of 5 mm and 7.5 mm. By means of scanning electronic microscopy, it was possible to see the more homogeneous hybrid layer in the cervical region of the root.